DUE TO THE LAW OF PEGADAIAN FIDUCIARY DEBTORS DEFAULT IN INDONESIA - Mieke Anggraeni Dewi; Mig Irianto Legowo; Darmawan Tri Budi Utomo (fakultas hukum universitas PGRI Semarang, 2023)
The existence of a guarantee object is that it still is in the hands of the fiduciary giving debtor in fiduciary guarantees often experience problems, including the fiduciary giving does not carry out its obligations to pay its debts resulting in default. therefore, the purpose of this study is to look at the legal consequences of defaulting on fiduciary debtors at Pegadaian companies and the obstacles faced in a study using a normative juridical approach with descriptive research specificationsThe results of the study show that in KREASI credit that has been registered in accordance with the provisions of the Fiduciary Law where if the debtor is in default, persuasive subpoena efforts will be made, the act of withdrawing the goods in the hands of the debtor until carrying out the execution in accordance with the provisions of Article 15 paragraph (1) of the UUF and the Constitutional Court Decision No. 18/PUU-XVII/2019. Whereas those who are not registered according to the provisions of Article 1155 paragraph 1 of the Civil Code Pawn companies can directly sell collateral objects that are in their control. Obstacles faced by PT Pegadaian if the debtor defaults, namely the debtor does not voluntarily hand over the collateral object, the collateral object has been damaged and no longer functions, and the collateral object is intentionally transferred by the debtor to a third party.